ESTABLISHMENT OF LOW-COST AQUAPONIC SYSTEM - Aglenieks, Lauris; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The goal of the project was to establish a low-cost sustainable food production system in a soilless environment which uses nutrient-rich water from fish clture. Also we known it as aquaponic systems, that combines aquaculture and soilless agriculture in closed-loop symbiotic systems. In this proces we check the quality of water using amonia, nitrites, nitrates and pH test kit and starting to grow lettuce, spring onions, persley and wrinkled pea. Study of this project shown how expensive is low-cost aquaponic system building and what kind of matereals you needed to build your own food production system.